2014
DOI: 10.1002/pca.2519
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Chromatography–Mass Spectrometry and Chemometric Analysis of Ricinus communis Extracts for Cultivar Identification

Abstract: Unique ions in extracts of 'carmencita', 'dehradun', 'gibsonii', 'impala' and 'zanzibariensis' were identified that would allow an individual cultivar to be distinguished from other cultivars in this study. Although 'sanguineus' extracts contained no unique compounds, a unique LC-MS profile would allow for cultivar assignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…Our results show that RCB-1 to 3 were compartmentalized differently among the embryo and testa tissues from different countries (Ethiopia, Pakistan, and China). For all castor bean sections from nine geographic origins, we did not find either RCB-4 or RCB-as Ovenden et al reported towards the "impala" cultivar from Tanzania (Ovenden et al, 2014). Due to the tissue heterogeneity, matrix coating heterogeneity, poor analyte extraction, and ionization suppression effects, the quantitative analysis of MALDI-MSI is still challenging.…”
Section: Distribution Of Rcbs In Castor Beanscontrasting
confidence: 58%
See 1 more Smart Citation
“…Our results show that RCB-1 to 3 were compartmentalized differently among the embryo and testa tissues from different countries (Ethiopia, Pakistan, and China). For all castor bean sections from nine geographic origins, we did not find either RCB-4 or RCB-as Ovenden et al reported towards the "impala" cultivar from Tanzania (Ovenden et al, 2014). Due to the tissue heterogeneity, matrix coating heterogeneity, poor analyte extraction, and ionization suppression effects, the quantitative analysis of MALDI-MSI is still challenging.…”
Section: Distribution Of Rcbs In Castor Beanscontrasting
confidence: 58%
“…RCB-1 and RCB-2 were commonly found in varying amounts in six different cultivars, while RCB-3 was found only in the "Carmencita" cultivar. After that, Ovenden et al identified RCB-4 and RCB-5 in the castor beans of the "impala" cultivar (Ovenden et al, 2014). Moreover, Fredriksson et al (Fredriksson et al, 2018) developed a method for chemical analysis of forensic attribution markers related to the purification of ricin based on a complex set of biomarkers including carbohydrates, fatty acids, RCBs, ricin, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis covered the detailed description of the carbohydrate and primary structure variants, and the results were compared to 10 ricin samples sourced from a total of seven different cultivars. Work conducted by Schieltz et al [ 47 ] elucidated the content of ricin in the beans from 18 different cultivars using isotope dilution mass spectrometry, other groups determined the Ricinus communis source cultivar by a LC-MS method [ 48 ] or based on a complex set of biomarkers using chemometric methods [ 49 ]. Our study encompassed novel strategies discovering the molecular features of ricin purified and analysed by applying a broad method portfolio and implementing combinatorial approaches.…”
Section: Discussionmentioning
confidence: 99%
“…From the acquired data, which include the exact molecular weight and fragment ions, both known and unknown compounds can be preliminarily identified by this processing method. Principal component analysis (PCA) and orthogonal partial least squares discriminant analysis (OPLS‐DA) are powerful tools for multiple factor statistical processing, and have been widely used in the screening of characteristic compounds in herbs and for classification (Ardila, Funari, Andrade, Cavalheiro, & Carneiro, ; Kamal et al, ; Ovenden, Pigott, Rochfort, & Bourne, ; Wang et al, ; Wang et al, ). Data processing allows for polytomized variables to be precisely screened out for dimensionality reduction analysis.…”
Section: Introductionmentioning
confidence: 99%